Accessibility Regulations and Tips for Reaching Older Adults and People with Disabilities - Debby Newman; Pam Prokop (Journal of Applied Communications, 2006)
Providing accessibility to all audiences is not just the right thing to do - it is the law. As a group, communicators have a responsibility to create accessible resources for people with disabilities, whether this involves classroom materials and press releases or online meetings. While communicators are not lawyers, we need to understand the essence of the statutes, since the United States Census Bureau (2006) reports that there are 51 million Americans with disabilities. This article describes the laws' requirements and ways for federally funded land-grant institutions to meet the intent of those laws. These institutions need to meet the requirements of the 1973 Rehabilitation Act (Section 504) the 1990 Americans with Disabilities Act (ADA) and Section 508, which amends the 1973 Rehabilitation Act to include software and Internet presentations. Applied communicators must make reasonable efforts to ensure that information products developed for people with disabilities are as effective as those developed for other audiences.